Optimizing the Role of Cash Waqf Linked Sukuk for State Development - Anindhita, Aulia Eka; Widana, IGN Oka (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
The Indonesian government has issued retail and non-retail Cash Waqf Linked Sukuk (CWLS). However, the cash waqf collected has not been optimal. This shows that public interests in retail CWLS are still low. Therefore, this study discusses possible ways to increase public interest in retail CWLS and optimize it for state development. Data is obtained from a literature review, interviews, and Focused-Group Discussion (FGD) with informants from the Indonesian Waqf Board (BWI), the Ministry of Finance, and academics. The results show stakeholders can promote CWLS through a social marketing approach. This is in line with the purpose of CWLS products, which is for social programs (non-profit oriented) carried out by the government and voluntary organizations. Furthermore, the design thinking method can be used to optimize the role of CWLS in state developments. Design thinking is a logical, systematic, and creative process that a person takes to experiment, produce ideas and model prototypes, and collect feedback. In this context, public literacy issues should be addressed, and the social programs financed should be formulated.   AbstrakPemerintah menerbitkan CWLS non-ritel dan CWLS retail, namun jumlah wakaf uang yang terkumpul belum maksimal. Ini menunjukkan rendahnya animo masyarakat terhadap produk CWLS ritel. Penelitian ini membahas care meningkatkan minat masyarakat pada produk CWLS ritel dan mengoptimalkan pemanfaatan CWLS dalam pembangunan. Data penelitian ini berasal dari kajian literatur, wawancara, dan Focus Group Discussion, dengan informant dari Badan Wakaf Indonesia (BWI), Kementerian Keuangan, dan akademisi. Hasil penelitian menunjukkan bahwa stakeholder dapat memasarkan produk melalui pengembangan teori pemasaran sosial karena tujuan dari produk CWLS adalah untuk program sosial masyarakat dan dilakukan oleh pemerintah bersama organisasi sektor sukarela. Selanjutnya, untuk mengoptimalkan peran CWLS pada pembangunan negara dapat menggunakan metode design thinking. Design thinking adalah proses logis, sistematis, dan kreatif yang dilakukan seseorang untuk bereksperimen, menghasilkan ide dan model prototipe, serta mengumpulkan umpan balik. Para Stakeholder harus menyelesaikan masalah literasi masyarakat dan pemilihan program sosial yang akan dibiayai terlebih dahulu.